Italian Playwrights from the Twentieth Century: A Companion Text - Vena, Michael (Xlibris Corporation, 2013)
Keywords: 20th century; History and criticism; Italian drama; dept.wll; faculty_collection

Refashioning the book in Pinochet's Chile: The feminist literary project. Ergo Sum - Cardone, R. (Confluencia, 2013)
Keywords: dept.wll; ⛔ No DOI found

Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature - Palma, Pina (University of Notre Dame Press, 2013)
"Pina Palma's Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature is an innovative look at the writings of five important Italian authors--Boccaccio's Decameron, Pulci's Morgante, Boiardo's Innamorato, Ariosto's Furioso, and Aretino's Ragionamento. Through the prism of gastronomy, Palma examines these key works in the Western literary canon, bringing into focus how their authors use food and gastronomy as a means to critique the social, political, theological, philosophical, and cultural beliefs that constitute the fabric of the society in which they live." -- Publisher's website.
Keywords: 16th century; History and criticism; Food in literature; Gastronomy in literature; History and criticism; Italian literature; Italian literature; SCSU Faculty Scholar Award; To 1400; award_winner; dept.wll; faculty_collection

Fairness - Scott Walters, F. (The Routledge Handbook of Language Testing, 2013)
Among language testing researchers, the notion of fairness has accumulated a number of complex, technical definitions over the years. However, since the word has such a widespread, everyday usage, consulting a dictionary can be a good starting-point for discussion. For example, YourDictionary.com (2011) states that to be fair is to be “just and honest,” “impartial,” and “unprejudiced,” specifically, “free from discrimination based on race, religion, sex, etc.“Merriam-Webster (Mish et al., 2003) states similarly that fairness is “marked by impartiality or honesty” and is “free from self-interest, prejudice, or favoritism.” As this volume deals with second/foreign/other language testing, it would seem appropriate (or perhaps one should say, fair) to include a dictionary definition crafted for L2 learners, as is this one from Cambridge (Walter et al., 2006): “Treating someone in a way that is right or reasonable, or treating a group of people equally and not allowing personal opinions to influence your judgment.”. © 2012 Selection and editorial matter, Glenn Fulcher and Fred Davidson.
Keywords: dept.wll

Students in the new millennium: how much do we know about them? - Wu, Jianxiong (Computer-Assisted Foreign Language Teaching and Learning: Technological Advances, 2013)
Vast and fast technological advancements mark the new millennium. New emerging technologies are changing the world and our society at a magnitude and scope never witnessed before. Who are our students in this new millennium? What do they look like? Are they a fundamentally different new generation as some claim, or do they still look similar to us in many ways? A clear understanding of the characteristics of our students is vitally important for our educational practice. The current study was conducted to contribute to this understanding. The findings of the study show that while students nowadays do enjoy a much broader access to new technology than students of the past, they still look similar to us in many ways. As educators, it is important for us to treat our students as individuals instead of just labeling them and placing them in a black and white dichotomy.
Keywords: Emerging technologies; Students; Technological advancement; Technology transfer; dept.wll

Developing cultural humility through critical service learning - Breda, Karen Lucas; Groot, Kim; Towle, Antoinette (Ciencia y enfermería, 2013)
Marked inequities or disparities in health care and health outcomes exist for millions in the United States of America. Urban apartheid and increasing social stratification separate social groups making it difficult for them to understand each other. Many U.S. health care professionals, including nurses, hold negative stereotypes toward the urban poor and disenfranchised. Creating vehicles for understanding and respect between health care professionals and the social groups they care for is needed. Cultural humility uses self-reflection, self-critique, openness and transcendence to address power inequities between providers and clients. "Critical service-learning" is a type of "service-learning" that adopts the tenets of critical theory and pedagogy in engaged partnerships to foster social responsibility and a justice-oriented framework. The purpose of this article is to showcase Project Horizon, an innovative university-based health and social advocacy partnership that uses critical service learning with the urban community to foster cultural humility. Project Horizon outcomes show that this long-term engaged partnership is an effective vehicle for developing and enhancing cultural humility among health care professionals participating in the endeavor. Implications: Replication of social and health advocacy projects such as the one conducted through Project Horizon can be made in other settings to increase the capacity for democratically oriented nurses and other health care professionals who have an enhanced sense of cultural humility.
Keywords: Critical service learning; Cultural humility; Health consortia; Health personnel; Healthcare disparities; dept.wll

Benedetta and the creation of ‘Second Futurism’ - Larkin, Erin (Journal of Modern Italian Studies, 2013)
Despite the recent vogue in studies on Futurism, writer and artist Benedetta Cappa Marinetti has received little critical attention. Few scholarly works have focused on her essays regarding woman and the Fascist state, and in particular the role of mother. It has been argued that these texts support not only the position that women futurists - in adhering to a movement remembered for its disprezzo della donna - were victims of their self-accepting inferiority, but also the view that Futurist attitudes towardswomen were a precursor of Fascist-era gender politics. Larkin challenges this position, and discusses crucial new archival research, which reveals how maternity in Benedetta's works is actually linked to her radical new reformulation of Futurism. Far from seconding woman's inferior position within the avant-garde, or indeed the Fascist state, Benedetta uses the issue of maternity subtly to subvert her status - in both the movement and society - from within. © 2013 Taylor & Francis.
Keywords: Avant-garde; Benedetta; Cappa; Futurism; Marinetti; Women writers; dept.wll